2021
DOI: 10.1186/s41687-021-00369-z
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of EQ-5D-5L as a routine outcome measure in Community Outpatient and Specialized Rehabilitation Services

Abstract: Rehabilitation is a person-centred approach that optimizes functioning to reduce impairments in individuals with illness, injury or disability. Patient-reported outcome measures (PROMs) have a role in rehabilitation to inform clinical practice, enhance patient-centered care, support health services programming, direct performance measurement, and contribute to quality improvement. A Canadian provincial health system implemented a Rehabilitation Model of Care that provides a real-world perspective on the adopti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The acceptability of the EQ-5D, from the perspectives of both clinicians and patients, is less clear. For some clinicians there is some concern that the EQ-5D lacks specificity and therefore, believe that it may not be applicable to their patients or practice [ 41 ]. While patients with chronic health conditions believe that it is easy to use and measures domains that are meaningful to them, but may not measure all relevant domains such as fatigue and medication side effects [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The acceptability of the EQ-5D, from the perspectives of both clinicians and patients, is less clear. For some clinicians there is some concern that the EQ-5D lacks specificity and therefore, believe that it may not be applicable to their patients or practice [ 41 ]. While patients with chronic health conditions believe that it is easy to use and measures domains that are meaningful to them, but may not measure all relevant domains such as fatigue and medication side effects [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results highlighted the contention between the positive attributes of a generic tool that is brief and broadly applicable to all conditions but at the expense of the level of detail often desired by clinicians from both a patient and discipline perspective. Previous research has shown that some clinicians find disease- or discipline-specific PROMs to be more valuable for informing and measuring clinical care outcomes than generic PROMS,[ 36 ] as generic PROMs may lack the specificity required to identify changes in health specific to the type of care provided [ 21 , 29 ]. In particular, the EQ-5D-5L lacked items relating to cognition, communication and diet, important aspects of health for speech pathologists, psychologists and dietitians.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the R-MoC, the EQ-5D-5L was adopted as a generic PROM and gradually implemented across community and outpatient rehabilitation services beginning in 2017. The process for selecting the EQ-5D-5L included stakeholder consultations, literature review, population needs assessment, current and future state reports, and a gap analysis [6]. Additionally, AHS had endorsed the EQ-5D-5L as the generic PROM for use in the healthcare system in 2015, and further embedding the ability to capture the EQ-5D-5L and other PROMs in Connect Care, the provincewide electronic patient medical information system [12].…”
Section: Introductionmentioning
confidence: 99%